Preface and acknowledgements. In idem, Corporatism and Fascism. The Corporatist Wave in Europe - Costa, António Costa (2018)
Pinto, A. C. (2017). Preface and acknowledgements. In idem, Corporatism and Fascism. The Corporatist Wave in Europe, pp. xi-xiii. Routledge Studies in Fascism and the Far Right. London and New York: Routledge.